Challenges in Developing Electrodes, Electrolytes, and Diagnostics Tools to Understand and Advance Sodium‐Ion Batteries. Issue 14 (12th February 2018) - Xu, Gui‐Liang; Amine, Rachid; Abouimrane, Ali; Che, Haiying; Dahbi, Mouad; Ma, Zi‐Feng; Saadoune, Ismael; Alami, Jones; Mattis, Wenjuan Liu; Pan, Feng; Chen, Zonghai; Amine, Khalil
Abstract: Considering the natural abundance and low cost of sodium resources, sodium‐ion batteries (SIBs) have received much attention for large‐scale electrochemical energy storage. However, smart structure design strategies and good mechanistic understanding are required to enable advanced SIBs with high energy density. In recent years, the exploration of advanced cathode, anode, and electrolyte materials, as well as advanced diagnostics have been extensively carried out. This review mainly focuses on the challenging problems for the attractive battery materials (i.e., cathode, anode, and electrolytes) and summarizes the latest strategies to improve their electrochemical performance as well as presenting recent progress in operando diagnostics to disclose the physics behind the electrochemical performance and to provide guidance and approaches to design and synthesize advanced battery materials. Outlook and perspectives on the future research to build better SIBs are also provided. Abstract : Room temperature sodium‐ion batteries show great promise for large scale electrochemical energy storage application because of the low cost and large abundance of sodium resource. The progress and main challenges regarding the development of electrode, electrolytes, and advanced diagnostics are summarized with the aim of achieving a high energy density of over 400 Wh kg −1 on the cell level.